2010
DOI: 10.1002/ppul.21156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of face mask dead volume, respiratory rate, and tidal volume on inhaled albuterol delivery

Abstract: In general, decreasing SDV, increasing VT, and increasing RR increase ACMO. Early transition from face mask to mouthpiece should be considered in children receiving albuterol via MDI with HC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 17 publications
1
25
1
1
Order By: Relevance
“…A previous study demonstrated that a larger dead space of the mask results in less albuterol delivered by pressurized metereddose inhaler (pMDI) to the mouth opening. 10 Therefore, masks designed to be used with pMDIs should ideally have a low dead space. However, no data are available regarding the effect of face mask dead space and nebulized drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that a larger dead space of the mask results in less albuterol delivered by pressurized metereddose inhaler (pMDI) to the mouth opening. 10 Therefore, masks designed to be used with pMDIs should ideally have a low dead space. However, no data are available regarding the effect of face mask dead space and nebulized drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…1,8 This technique has limited value, as it usually requires that the mask be placed against a smooth, flat surface. However, children's faces are far from flat, and moreover, they develop and grow continuously and relatively rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Chavez et al 1 studied albuterol delivery via an AeroChamber and showed that greater dead space of a mask attached to this chamber resulted in less efficient aerosol delivery for the same V T . 1 Thus, the V D of a face mask is a very important determinant of face-mask design, 3 particularly in infants and small children with low V T . The mean V T in infants 9 months old was recently documented as 81.5 Ϯ 28.2 mL, with a mean V T of 9.7 Ϯ 1.3 mL/kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yüz maskesi uygun bir şekilde yüze oturtulmalı, yüzle temas ettiği bölgede hava kaçışı engellenmelidir. Ölü boşluğu azaltmak için mümkün olan en kısa sürede ağızlıklı kullanıma geçil-melidir (14).…”
Section: Araci Tüpunclassified